2020
DOI: 10.3390/cancers12102925
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of LncRNAs Binding to Protein in Carcinogenesis

Abstract: Epigenetic dysregulation is an important feature for cancer initiation and progression. Long non-coding RNAs (lncRNAs) are transcripts that stably present as RNA forms with no translated protein and have lengths larger than 200 nucleotides. LncRNA can epigenetically regulate either oncogenes or tumor suppressor genes. Nowadays, the combined research of lncRNA plus protein analysis is gaining more attention. LncRNA controls gene expression directly by binding to transcription factors of target genes and indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 132 publications
0
14
0
Order By: Relevance
“…LncRNA can crosstalk with chromatin, DNA, RNA, and proteins, regulating GC cell progression via transcriptional and posttranscriptional mechanisms ( Kong et al, 2018 ; Zhuo et al, 2019 ). The cellular distribution of lncRNAs is informative for lncRNA functions ( Shin et al, 2020 ). A large number of lncRNAs function by binding to a protein partner ( Castello et al, 2016 ; Chen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA can crosstalk with chromatin, DNA, RNA, and proteins, regulating GC cell progression via transcriptional and posttranscriptional mechanisms ( Kong et al, 2018 ; Zhuo et al, 2019 ). The cellular distribution of lncRNAs is informative for lncRNA functions ( Shin et al, 2020 ). A large number of lncRNAs function by binding to a protein partner ( Castello et al, 2016 ; Chen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the mechanism by which HOTAIRM1 regulates the malignant phenotype of tMSCs, subcellular localization of HOTAIRM1 was detected by qRT-PCR. The results showed that HOTAIRM1 was mainly existed in nucleus (Figures 3(a) - 3(b) ) which indicated that HOTAIRM1 plays regulatory roles via recruiting RNA-binding proteins (RBPs) [ 27 , 28 ]. Next, starBase was used to search the RBPs to which HOTAIRM1 could bind, and five RBPs were screened out.…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic mechanisms such as histone modifications, DNA methylation, non-coding RNAs and chromatin remodeling were proved to regulate gene expression by many cross talk ways 5 . DNA methylation is one of the most widely studied epigenetic mechanisms, which is a covalent modification of DNA, plays an important role in the regulation of genome function, often occurs in hepatocellular carcinoma, bladder cancer, prostate cancer and many other common cancers 6 .…”
Section: Introductionmentioning
confidence: 99%